MANAJEMEN PERENCANAAN DAN PENGELOLAAN KEUANGAN (BOS) SEKOLAH DASAR DI KOTA PADANG - Risdal Yosli; Kasman Rukun; Muhammad Giatman (STKIP Pesisir Selatan, 2020)
In general, management is the management of a job to get results in order to achieve the goals that have been determined by moving other people to work. School financial planning is a process for determining the appropriate future financial actions of a school, through a sequence of choices, taking into account the financial situation available. School financial management or School Operational Assistance financial is carried out directly by the school, but is guided and supervised by the education office. The school that is given authority, based on the ability of School Based Management, manages school finances based on the BOS technical guidelines and technical guidelines from the city BOS manager. Financial management is carried out through the stages of planning, realization and reporting. The smooth management of school finances depends on good management, starting from the decision maker to the lowest level, namely the school. The smoothness of financial management has an impact on other fields in the administration of education, such as the purchase of student needs, office needs, teaching staff and educational needs.